HIF signaling pathway in pheochromocytoma and other neuroendocrine tumors - Jochmanová, I; Zelinka, T; Widimský, J; Pacak, K (Physiological research, 2014)
Hypoxia-inducible factors (HIFs) are transcription factors controlling energy, iron metabolism, erythropoiesis, and development. Dysregulation of these proteins contributes to tumorigenesis and cancer progression. Recent findings revealed the important role of HIFs in the pathogenesis of neuroendocrine tumors, especially pheochromocytoma (PHEO) and paraganglioma (PGL). PHEOs and PGLs are catecholamine-producing tumors arising from sympathetic- or parasympathetic-derived chromaffin tissue. To date, eighteen PHEO/PGL susceptibility genes have been identified. Based on the main signaling pathways, PHEOs/PGLs have been divided into two clusters, pseudohypoxic cluster 1 and cluster 2, rich in kinase receptor signaling and protein translation pathways. Recent data suggest that both clusters are interconnected via the HIF signaling and its role in tumorigenesis is supported by newly described somatic and germline mutations in HIF2A gene in patients with PHEOs/PGLs associated with polycythemia, and in some of them also with somatostatinoma. Moreover, HIFalpha signaling has also been shown to be upregulated in neuroendocrine tumors other than PHEO/PGL. Some of these tumors are components of hereditary tumor syndromes which can be associated with PHEO/PGL, but also in ileal carcinoids or melanoma. HIF signaling appears to be one of the crucial players in tumorigenesis, which could suggest new therapeutic approaches for treatment of neuroendocrine tumors.
Keywords: feochromocytom; signální transdukce; transkripční faktory bHLH; nádory nadledvin; Signal Transduction; faktor 1 indukovatelný hypoxií - podjednotka alfa; Prognosis; Animals; Humans; prognóza; lidé; Adrenal Gland Neoplasms; Neuroendocrine Tumors; zvířata; Hypoxia-Inducible Factor 1, alpha Subunit; Pheochromocytoma; neuroendokrinní nádory; Basic Helix-Loop-Helix Transcription Factors